Bezpieczeństwo osób z niepełnosprawnościami w kontekście funkcjonowania systemu zarządzania kryzysowego w Polsce .......... 203 - Szmitkowski, Paweł (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
The protection of people with disabilities in situations of threats bearing the signs of natural disasters and catastrophes, and thus extraordinary dangers, is one of the most serious challenges for the crisis management system, which is the key entity in Poland responsible for ensuring the safety of civilians in such situations. However, the current state of system preparation in this respect is far from satisfactory. Serious legal, organizational or task deficits should be highlighted. Therefore, there is a need to immediately undertake research, the aim of which should be to make appropriate modifications to the CMS in such a way that it is able to guarantee comprehensive safety for people with disabilities on an equal basis with the rest of society.